Mapping Schools Vulnerability to Earthquakes: Case Study of Cianjur Earthquake 21 November 2022 - Yani Yani; Tusam Mohamad; Larasaty Dwi; Isnaini Nur (E3S Web of Conferences)
Earthquakes are unpredictable disasters that cause a lot of damage, such as the destruction of infrastructure and casualties. Indonesia has a high level of earthquake risk. One of the earthquakes that occurred was the Cianjur earthquake in November 2022, caused by the movement of the Cugenang fault. This earthquake caused many houses and public facilities, including schools, to be damaged. This study aims to map schools that are vulnerable to earthquakes as one of the early warning systems to improve disaster preparedness. The classification is based on the earthquake vulnerability map provided by BMKG. The research method used is Geographic Information System (GIS). Data from the earthquake hazard map and the distribution of schools were then analyzed using the overlay technique. From the results of this processing, three earthquake hazard zones were determined, namely the forbidden zone, the restricted zone, and the conditional zone. There are two schools with a percentage of 6.45% in the forbidden zone, seven schools with a percentage of 22.58% in the restricted zone, and 22 schools with a percentage of 70.97% in the conditional zone. More schools are in the conditional zone; therefore, it is necessary to increase earthquake disaster awareness.